The Effectiveness of the South Kalimantan Community and Community Service Unit in Reducing Traffic Violations Traffic at the Kediri City Police Station (Indonesian Journal of Police Studies, 2024)
The problem of the high number of traffic violations in Kediri City disrupts security, safety, order, and smooth traffic. This study aims to evaluate the effectiveness of Dikmas Lantas activities carried out by the Kamsel Unit at the Kediri City Police Station in reducing traffic violations. A qualitative approach is used with data collection through observation, interviews, and document studies. Data analysis refers to Hasibuan Effectiveness Theory and Henry Fayol's Management Theory. The results showed that Dikmas Lantas activities have not taken place effectively because the quantity and quality of work is still lacking, as well as inadequate human resources. Matters that affect the continuity of Dikmas Lantas activities include planning, organizing, giving orders, coordinating, and supervising. Suggestions that can be implemented include meeting activity targets, improving material delivery, effective task distribution, making pamphlets and banners urging orderly traffic, and creating Satlantas WhatsApp channels. It is hoped that by implementing these suggestions, Dikmas Lantas activities can be more effective in reducing traffic violations in Kediri City.
Keywords: Efektivitas, Dikmas Lantas, Unit Kamsel, Pelanggaran Lalu Lintas.